University Of Minnesota Football Stadium Down Hole Pile: Innovative Solution For Difficult Conditions - Eric J. Pederson (Deep Foundations Institute, 2008)
The down hole hammer is widely used in specialty geotechnical construction. The common uses include tie-back anchor installation, micropile installation, and general soil/bedrock drilling operations. Veit used these techniques to develop a cost effective way of installing the foundation system for University of Minnesota Football Stadium. The soils present at the site of the stadium contained layers of concentrated cobbles and boulders. The geotechnical engineer recommended a driven pile system, and the base bid outlined in the project documents consisted of an H-Pile using a 14x73 pile section. Veit submitted an innovative alternate consisting of using a rotary percussion system to install a 12? O.D. pile. This paper will show that this pile type and installation method was the correct choice for the project. The design criteria for the compression, uplift, and lateral capacities and deflections were met, while eliminating pile damage. The method resulted in a significant cost savings to the University and maintained the project schedule.